Cross-Cultural Perspectives on Intimacy and Communication in Marriage: Adapting Marriage Counseling Approaches for Diverse Cultural Contexts - Arahman, Zulfikar; Chai, Nong; Lima, Lucas (International Journal of Research in Counseling, 2024)
This study investigates the critical role of cross-cultural perspectives in understanding intimacy and communication within marriage. As societies become increasingly diverse, traditional marriage counseling approaches often overlook the unique needs and experiences of couples from varied cultural backgrounds. This article aims to explore how cultural values, norms, and communication styles shape the experiences of intimacy and influence relationship dynamics among married individuals. The research highlights that intimacy is not merely a personal experience but is heavily influenced by cultural context, which dictates how affection, emotional support, and conflict resolution are perceived and expressed. By analyzing various counseling models, including those that are culturally informed, this study emphasizes the need for adaptability in therapeutic practices. It also discusses the potential barriers that culturally diverse couples face in counseling settings, such as misinterpretation of behaviors and expectations rooted in differing cultural backgrounds. Furthermore, the article provides practical recommendations for marriage counselors to create more inclusive and effective interventions. This includes the necessity of integrating cultural competence training into counselor education programs and developing tailored counseling strategies that acknowledge and respect cultural differences. By doing so, counselors can better support couples in navigating their unique challenges and enhancing their relational satisfaction. Ultimately, this study advocates for a shift in marriage counseling paradigms to embrace a more holistic and culturally sensitive approach, thereby improving outcomes for couples from diverse backgrounds.